The investigation on stability and physicochemical properties of multi ferrites nanoparticles dispersed Tamarindus indica biodiesel - Kannam Sree Sruthi; Sathya Vara Prasad Lankapalli; Jaikumar Sagari (International Journal of Thermofluids)
This study aims to investigate the stability and physicochemical properties of nickel and manganese doped bismuth ferrite nanoparticles (BNiFMO) in a Tamarindus indica biodiesel. The BNiFMO nanoparticles were evaluated at concentrations of 50 mg/L and 75 mg/L. In addition, the BNiFMO nanoparticles were supplemented with dispersants (Tritonx and QPAN) at different ratios, namely 1:0.25, 1:0.5, 1:0.75 and 1:1, respectively. The stability study was carried out using the principle of photo spectroscopy at three different time intervals: Week 1, 2 and 3. The stability was evaluated by transmittance and absorbance. In addition, the physicochemical properties were evaluated according to ASTM standards. The transmittance of BNiFMO nanofuel spiked with Tritonx and QPAN80 was lower compared to the base nanofuel, while the absorbance increased, indicating better stability. At lower ratios of nanoparticles and Tritonx/QPAN, stability decreased, but better stability was achieved at a 1:1 ratio. The QPAN-based nanofuel was found to be more stable overall than the base nanofuel and the Tritonx-based nanofuel. The lower transmittance and higher absorbance were noticed with B20 + BNiFMO75 mg/L + QPAN 75 mg/L, while the stability decreased slightly with increasing duration. The minimum transmittance and higher absorbance values recorded were 87.75 % and 4.42 in week 1, 89.93 % and 4.23 in week 2, and 91.21 % and 4.18 in week 3. Finally, the addition of Tritonx and QPAN to BNiFMO nanofuel led to an increase in calorific value and cetane number. The highest calorific value and cetane number recorded were 41.456 MJ/kg and 64, respectively, for the B20 + BNiFMO 75 mg/L + QPAN 75 mg/L blend. However, the kinematic viscosity and density exhibited somewhat inconsistent trends.